2022
DOI: 10.1101/2022.07.19.500618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A physical neural mass model framework for the analysis of oscillatory generators from laminar electrophysiological recordings

Abstract: Cortical function emerges from the interactions of multi-scale networks that may be studied at a high level using neural mass models (NMM), which represent the mean activity of large numbers of neurons. In order to properly reproduce experimental data, these models require the addition of further elements. Here we provide a framework integrating conduction physics that can be used to simulate cortical electrophysiology measurements, in particular those obtained from multicontact laminar electrodes. This is ach… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Superficial to deep layer volume conduction has been proposed to explain why alpha/beta power appears relatively more powerful in superficial layers when calculated on CSD signals 13,34 – the opposite pattern that we observe in the unipolar LFP referenced to the top of cortex. Recent biophysical modeling, however, suggests an alternative interpretation: an alpha/beta power peak in deep layers in the local field potential (referenced to the top of cortex, as we have done in the present study) together with a superficial CSD power peak (as observed by 13,34 ) can both be modeled by considering the elongated cell bodies of deep layer pyramidal neurons which receive synaptic inputs in both their apical dendrites in superficial layers as well as near the cell body in deep layers 49,50 . This modeling work suggests that the alpha/beta-generating circuitry includes both superficial and deep layers and is more spatially extended (extends into deeper layers) than the gamma-generating circuitry.…”
Section: Discussionmentioning
confidence: 67%
“…Superficial to deep layer volume conduction has been proposed to explain why alpha/beta power appears relatively more powerful in superficial layers when calculated on CSD signals 13,34 – the opposite pattern that we observe in the unipolar LFP referenced to the top of cortex. Recent biophysical modeling, however, suggests an alternative interpretation: an alpha/beta power peak in deep layers in the local field potential (referenced to the top of cortex, as we have done in the present study) together with a superficial CSD power peak (as observed by 13,34 ) can both be modeled by considering the elongated cell bodies of deep layer pyramidal neurons which receive synaptic inputs in both their apical dendrites in superficial layers as well as near the cell body in deep layers 49,50 . This modeling work suggests that the alpha/beta-generating circuitry includes both superficial and deep layers and is more spatially extended (extends into deeper layers) than the gamma-generating circuitry.…”
Section: Discussionmentioning
confidence: 67%
“…In KT, this is the neurobiological realization of the Comparator, which is reflected in the canonical microcircuit. In the concept of cortical canonical microcircuits, the cortical column is a motif replicated with minor variations in the cortex that contains the elements necessary to perform computations [Bastos et al, 2018;Sanchez-Todo et al, 2022], and where feedback and feed-forward information streams merge for comparison of data and models via the summation of excitation and inhibition signals.…”
Section: Canonical Microcircuitry and Dendritic Integration Theory (Dit)mentioning
confidence: 99%
“…The integration of these aspects is crucial for solving the SEEG-forward problem and hence simulating realistic SEEG signals. The present model includes a laminar architecture that represents the cortical layers of the human brain, following the framework in [30,31] and also used in [32] for the analysis of seizure data. A laminar representation of a human cortical column of six layers with a physiological thickness [33] and uniform conductivity σ = 0.3 × 10 −3 S mm −1 [34] was considered.…”
Section: Computational Modelmentioning
confidence: 99%